Adult vaccination in India: status and the way forward - Chandrakant Lahariya; Pankaj Bhardwaj (Taylor & Francis Group, 2020)
In the last two decades, the childhood vaccination coverage in most low and middle-income countries including India has increased. Additional vaccines are being offered through national immunization programs as well as through private sector and the benefits of vaccination are reaching to more children than ever. This has resulted in major decrease in vaccine preventable diseases and contributed to decline in the morbidity and mortality rates. This development is expected to result in epidemiological transition (which is already happening) and mandates for policies and strategies to extend the benefit of available vaccines and vaccination beyond traditionally target age groups to include the adults, elderly and the at-risk populations. This article reviews the present status of adult vaccination in India and proposes a few approaches to move towards life course vaccination.